Complementary and Alternative Medicine Treatment Options for Otitis Media: A Systematic Review - Marom, Tal (Medicine (Baltimore), 2016)
Otitis media (OM) has numerous presentations in children. Together with conventional medical therapies aimed to prevent and/or treat OM, a rising number of complementary and alternative medicine (CAM) treatment options can be offered. Since OM is common in children, parents may ask healthcare professionals about possible CAM therapies. Many physicians feel that their knowledge is limited regarding these therapies, and that they desire some information. Therefore, we conducted a literature review of CAM therapies for OM, taking into account that many of these treatments, their validity and efficacy and have not been scientifically demonstrated. We performed a search in MEDLINE (accessed via PubMed) using the following terms: “CAM” in conjunction with “OM” and “children. Retrieved publications regarding treatment of OM in children which included these terms included randomized controlled trials, prospective/retrospective studies, and case studies. The following CAM options for OM treatment in children were considered: acupuncture, homeopathy, herbal medicine/phytotherapy, osteopathy, chiropractic, xylitol, ear candling, vitamin D supplement, and systemic and topical probiotics. We reviewed each treatment and described the level of scientific evidence of the relevant publications. The therapeutic approaches commonly associated with CAM are usually conservative, and do not include drugs or surgery. Currently, CAM is not considered by physicians a potential treatment of OM, as there is limited supporting evidence. Further studies are warranted in order to evaluate the potential value of CAM therapies for OM.